Policy Implementation of Governmental Institution Performance Accountability (AKIP) That is Embodied in The Report of Governmental Institution Accountability (LAKIP) - Joko Widodo (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
Accountability is an important value in the governmental operation. To know the governmental accountability level, it should be arranged measurement and reporting system. Governmental Institution performance Accountability System (SAKIP) is responsibility instrument that consist of some indicators and measurement activity mechanism, assessment, and performance reporting comprehensively and integrally to fulfill the obligation of certain governmental institution in responsible for success/failure in the main task execution and function and the organizational mission. The research aimed at knowing the process, results, and impact of governmental performance accountability policy execution (AKIP) that is embodied in the form of Governmental Institution Accountability Report (LAKIP). Based on process evaluation standard and field finding results, it is concluded that the AKIP policy implementation process in the form of LAKIP can be said ”not success yet”, although procedurally and in format the LAKIP has been suitable with the determined guideline, but substantially found many inappropriateness or incompletion yet of each SAKIP component as the process evaluation standard.Keywords: accountability, government, performance